Associations Between Timing of Meals, Physical Activity, Light Exposure, and Sleep with Body Mass Index in Free-Living Adults - Marinac, Catherine R. (J Phys Act Health, 2019)
BACKGROUND: This study tested if the timing of meals, physical activity, light exposure, and sleep cluster within individuals and are associated with Body Mass Index (BMI) in a sample of free-living adults (n=125). METHODS: Data were collected between November 2015 and March 2016 at UC San Diego, Children’s Hospital of Philadelphia, and Washington University in St. Louis. Height and weight were measured and BMI (kg/m(2)) was calculated. Sleep timing was estimated using actigraphy; and timing of meals, physical activity, and light exposure were self-reported using a smartphone application. General linear models estimated the mean BMI across time categories of behaviors, adjusting for covariates. A latent class analysis was used to identify patterns of timing variables that clustered within individuals and test for associations between identified patterns and BMI. RESULTS: Later exposure to outdoor light was associated with a lower BMI (P-trend<0.01). The timing of other behaviors were not independently associated with BMI. The latent class analysis identified two distinct groups related to behavioral timing, reflecting an “early bird” and “night owl” phenotype. These phenotypes were not associated with BMI (P>0.05). CONCLUSIONS: Timing of exposures to light, meals, sleep, and physical activity were not strongly associated with BMI in this sample.